Palliative sedation (part I). Controversies about terms, definitions and clinical applications - Taboada R., Paulina (Acta Bioethica, 2012)
This article analyzes the use of palliative sedation, as a potentially useful therapeutic tool in Palliative Medicine. It suggests that, in spite of the improvement of medical knowledge related to palliative sedation during the last decade, available empirical evidence is still limited and controversy persists. The current debate includes aspects such us: 1. The definition and terminology (palliative vs. terminal sedation); 2. The types of sedation that are included under these expressions (intermittent vs. continuous; superficial vs. profound); 3. The clinical indications (physical symptoms vs. existential suffering); 4. The concomitant administration vs. withdrawal of medically assisted nutrition and hydration; 5. The ethical foundations and its difference with euthanasia and/or physician-assisted-suicide. This article analyzes aspects related to the concept of “palliative sedation” and its different definitions, as well as some controversies related to its clinical applications. Although ethical issues related to palliative sedation are briefly mentioned, they are not dealt with in this article, but intentionally left for a deeper analysis in a part II.